Choline-chloride-based eutectic solvent for the efficient production of docosahexaenoyl and eicosapentaenoyl ethanolamides via an enzymatic process - Tan, Chin Ping; Liang, Hui Pei; Qin, Xiaoli; Daoming, Li; Wang, Yonghua (American Chemical Society, 2018)
Docosahexaenoyl and eicosapentaenoyl ethanolamides (DHEA and EPEA) have physiological functions, including immunomodulation, brain development, and anti-inflammation, but their efficient production is still unresolved. In this study, choline-chloride-based natural deep eutectic solvents are used as media to improve the production of DHEA and EPEA. The water content showed a key effect on the reactant conversion. Adding water to choline chloride–glucose (CG, molar ratio of 5:2) led to a significant increase (13.03% for EPEA and 27.95% for DHEA) in the yields after 1 h. The high yields of EPEA (96.84%) and DHEA (90.06%) were obtained under the optimized conditions [fish oil ethyl esters/ethanolamine molar ratio of 1:2, temperature of 60 °C, 1 h, enzyme loading of 2195 units, and CG containing 8.50% water of 43.30% (w/w, relative to total reactants)]. The products could be easily separated using centrifugation. In summary, the research has the potential to produce fatty acyl ethanolamides.